Analytical methods and application of stable isotopes in dissolved organic carbon and inorganic carbon in groundwater. (25th August 2015) - Zhou, Yinzhu; Guo, Huaming; Lu, Hai; Mao, Ruoyu; Zheng, Hao; Wang, Jun
<x xml:space="preserve">Abstract</x> Rationale The stable isotopes of dissolved organic carbon (DOC) and inorganic carbon (DIC) provide insights into the carbon cycle, biogeochemical processes, and the fate of redox‐sensitive elements in groundwater systems. The simultaneous determination of the stable isotope ratios (δ13CDIC and δ13CDOC values) in DIC and DOC in water samples would provide better understanding of those processes. Methods The conditions for pretreating water samples prior to determining their DIC and DOC stable isotope ratios were optimized with a series of experiments on pre‐purging (GasBench needle versus blowing concentrator) and reaction conditions. The carbon stable isotope ratios were determined by isotope ratio mass spectrometry. Sequential determination of the δ13CDIC and δ13CDOC values was also carried out using the optimized conditions. National Institute of Standards and Technology (NIST) δ13C standards were utilized to verify the precision of the proposed method. Results The optimized pretreatment conditions for DIC isotope analysis involved pre‐purging the empty sample bottle for 60 min using a pressurized helium gas‐blowing concentrator and then reacting the sample with 85% H3PO4 for 60 min in a water bath at 60°C. The optimized pretreatment conditions for DOC isotope determination involved pre‐purging the sample for 60 min with the pressurized helium gas‐blowing concentrator after adding 0.1 mol L–1 AgNO3 and 85% H3PO4 and then reacting with Na2S2O8 as an oxidant and AgNO3 as a catalyst, in a 100°C water bath for 60 min. Conclusions With the optimized methods, the analytical precision of the δ13CDIC and δ13CDOC values of the reference samples was 0.02‰. The precision of δ13CDIC and δ13CDOC values in groundwater samples was 0.03‰ and 0.17‰, respectively. For the sequential determination of the DIC and DOC carbon isotope ratios, the precision of the δ13CDIC and δ13CDOC values in reference samples was better than 0.2‰. Copyright © 2015 John Wiley & Sons, Ltd.